2011
DOI: 10.1111/j.1365-2745.2011.01809.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecotypes of European grass species respond differently to warming and extreme drought

Abstract: Summary1. Climate extremes are expected to increase in frequency and magnitude as a consequence of global warming. 2. Managed permanent grasslands cover a large surface in Europe and contribute substantially to agricultural production. These managed plant communities are dominated by perennial clonal species. Their capacity to adapt to rapidly changing environmental conditions may be limited. 3. We hypothesize that those plant populations that have already been exposed to conditions that are expected to occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
95
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 45 publications
6
95
2
Order By: Relevance
“…Experimental evidence suggests that conventional SDM is not able to properly capture the climatic response of species by treating them as homogeneous units (Beierkuhnlein et al, 2011). With this regard, Hernández et al (2006) suggested that research in environmental niche modelling should focus on broad distributional subunits based on distinct genetic linages.…”
Section: Species Datamentioning
confidence: 99%
“…Experimental evidence suggests that conventional SDM is not able to properly capture the climatic response of species by treating them as homogeneous units (Beierkuhnlein et al, 2011). With this regard, Hernández et al (2006) suggested that research in environmental niche modelling should focus on broad distributional subunits based on distinct genetic linages.…”
Section: Species Datamentioning
confidence: 99%
“…The capacity of an ecosystem to adapt to or absorb the effects of a severe event depends on the severity and longevity of the event (Barrett et al 2008) and the tolerance range of the species present (Beierkuhnlein et al 2011). Once the capacity to absorb impact is exhausted, severe events can have sudden and long-lasting effects, often pushing ecosystems over thresholds towards other regimes (Allen & Breshears 1998) where recovery may be prolonged or not possible (Beisner, Haydon & Cuddington 2003).…”
Section: Introductionmentioning
confidence: 99%
“…There is also increasing evidence for high intraspecific variability in species responses to extremes, which has been observed to be of equal or even greater magnitude than interspecific variation [51]. High intraspecific variability may be influenced by ecotypic and genetic variation within a species ( [37,52,53], but see [54]). High intraspecific trait variation has thus been posited to contribute to post-extreme shifts in community-weighted trait means irrespective of gains or losses of species from the community [55].…”
Section: Scaling Individual Plant Responses To the Population And Commentioning
confidence: 99%